The Idea of a University in the Post-Covid-19 World - LenkaBula, Puleng (West African Journal of Open and Flexible Learning, 2022)
Historically, pandemics have forced humans to break with the past and imagine their world anew. This one is no different. It is a portal, a gateway between one world and the next. We can choose to walk through it, dragging the carcasses of our prejudice and hatred, our avarice, our data banks and dead ideas, our dead rivers and smoky skies behind us. Or we can walk through lightly, with little luggage, ready to imagine another world. And ready to fight for it.Arundhati Roy, Azadi: Freedom, Fascism, Fiction, 2020